The Effect of Openings on Thermal Comfort of Residential Building: Case study in Bandar Lampung - Arminda, Wenny; Puspitasari, Dian; Mohd Arshard, Wan Nur Rukiah; Caisarina, Irin (Jurnal RAUT, 2024)
A good residence must be able to provide comfort, especially thermal comfort, so that it is comfortable to carry out activities in it. This can be done through openings such as windows, ventilation, doors or casing as a way for air to enter and exit. Openings are the main factor that influences the temperature and humidity of the air in a residential house. This research aims to evaluate the thermal comfort conditions of residential homes by analyzing openings, temperature and air humidity. Furthermore, this research also uses the Autodesk Ecotect Analysis 2011 application simulation on the design solutions provided to maximize the wind entering the house. This research uses descriptive and exploratory quantitative methods. Research results from case studies show that openings greatly influence air temperature which ultimately affects the thermal comfort of residential homes. The right shape, dimensions and orientation of window openings can make the air temperature cool and comfortable.